PEMANFAATAN BIOFERTILIZER KELOR UNTUK EFEKTIVITAS SMART FARMING BERBASIS GREEN HOUSE - Susanto, Hendra; Taufiq, Ahmad; Sunaryono, Sunaryono; Gunawan, Ari; Sholeh , Moch (SEMANGGI : Jurnal Pengabdian kepada Masyarakat, 2023)
In an effort to utilize the potential of Moringa leaves in Sumenep Regency, this service team proposes marketing of Moringa leaf products based on considerations from RIRN 2017-2045, RENSTRA UM, and KAPUS PHIKA LP2M UM. [Situation analysis] Moringa tree is a type of plant that is very easy to breed, grow and cultivate on community land, either in fields, gardens, the edges of rice fields and people's house yards. Moringa plants have many benefits that are spread in every part, ranging from leaves, seeds, stems, and roots. Moringa plants are able to overcome nutritional deficiencies and various health problems because they have a high nutritional content. Moringa also has potential as a raw material for medicines, cosmetic industry and environmental improvement from pollution with a high level of market demand. [Partner problems] Currently, partners need synergy to utilize the potential of natural materials for farming purposes (local resources), fruit farmers experience crop failure due to the drastic climate. [Solution] The UM service team offers a solution in the form of socialization and assistance for Moringa products, namely MOLP based on Green House agriculture. [Objective] The main objective in this service activity is to establish partnerships to take advantage of available business opportunities (utilization of Moringa leaves) and assist farmers' complaints regarding weather problems, in order to meet local and foreign market demands. The results of this service activity are expected to make Moringa plants a source of income for the people of Sumenep Regency (the supplier of MOLP). Furthermore, it is also expected to be able to increase synergy with the government in order to build domestic food security. [Method of implementation] This service activity will be carried out through a process of observation, planning, mentoring, and socialization.